A new species of the genus Curculio Linnaeus, 1758 (Coleoptera: Curculionidae) from Hungary and the Balkan Peninsula - Szénási, Valentin (Zootaxa, 2022)
The new species Curculio gyongyiae sp. nov. from Hungary, Croatia and Greece is described and illustrated. A key for identifying the Hungarian Curculio and a map of distribution of the new species in Hungary are also given.